Back Cover. Issue 4 (29th March 2021) - Unknown
Abstract : The electrochemical thiocyanation/cyclization of aldehyde hydrazones was developed by a mild, direct electrolysis manner in an undivided cell without the additive of halogens and external oxidants. In this protocol, commercially available and inexpensive sodium thiocyanate was used, which played a dual role as a thiocyanation reagent and electrolyte. More details are discussed in the article by Ruan et al . on page 942—946. Abstract : The electrochemical thiocyanation/cyclization of aldehyde hydrazones was developed by a mild, direct electrolysis manner in an undivided cell without the additive of halogens and external oxidants. In this protocol, commercially available and inexpensive sodium thiocyanate was used, which played a dual role as a thiocyanation reagent and electrolyte. More details are discussed in the article by Ruan et al . on page 942—946.